SISTEM INFORMASI PELANGGAN (SINGGAN) PDAM KOTA DENPASAR BERBASIS ANDROID - Joko Santoso; I Made Darma Susila; I Putu Oka Juliantara (Jurnal Teknologi Informasi dan Komputer, 2020)
ABSTRACTPDAM Denpasar is the Regional Water Company in the city of Denpasar. Now, PDAM Denpasaralready has a Customer Information System however there are still deficiencies in the delivery ofinformation to customers and attract new customers. Registration of new customers and the surveywas handled by officers and required time to carry out the registration and surveys. In addition,potential customers should also visit the counters PDAM Denpasar to being recorded, and submit theregistration requirements. The development of smart phone technology with the mobile operatingsystem greatly facilitates the development of applications that aim to overcome these problems. So thequeues in the submission of the registration requirement can be reduced and the registration processbecomes shorter. Results of the research is a SINGGAN application that can handle customerregistration process, Customer Surveys, Monthly Checking Account, Report Stan and CustomerComplaints in one application that allows customers to access the service.Keywords: SINGGAN, android, PDAMABSTRAKPDAM Kota Denpasar merupakan Perusahaan Daerah Air Minum untuk wilayah Kota Denpasar. Saatini, telah memiliki Sistem Informasi Pelanggan namun masih terdapat kekurangan dalam penyampaianinformasi kepada pelanggan dan menjaring pelanggan baru. Pendaftaran pelanggan baru dan surveimasih ditangani oleh petugas dan diperlukan waktu untuk melakukan pendaftaran dan survei. Selainitu, calon pelanggan juga harus mengunjungi loket-loket PDAM Kota Denpasar untuk didata danmenyerahkan persyaratan pendaftaran. Perkembangan teknologi ponsel cerdas dengan sistem operasimobile sangat memudahkan dalam pembangunan aplikasi yang bertujuan untuk mengatasipermasalahan tersebut. Sehingga antrian dalam penyerahan persyaratan pendaftaran dapat dikurangidan proses pendaftaran menjadi lebih singkat. Hasil penelitian berupa aplikasi SINGGAN yang dapatmenangani proses Pendaftaran Pelanggan, Survei Pelanggan, Pengecekan Rekening Bulanan, LaporStan dan Keluhan Pelanggan dalam satu aplikasi yang memudahkan pelanggan mengakses layanantersebutKata Kunci : SINGGAN, android, PDAM